AN ANALYSIS OF ELEVENTH-GRADE STUDENTS' ABILITY TO WRITE SHORT STORIES BASED ON PERSONAL EXPERIENCE - Thresia Trivict Semiun; Delicia Abani (LPPM Universitas Islam Darul `Ulum Lamongan, 2025)
This study examined eleventh-grade students' ability to write short stories based on personal experience at SMAN 2 Kefamenanu. The main focus of this research was to analyze five aspects of writing short stories, namely content, organization, grammar, mechanics, and vocabulary, as well as the level of ability and difficulty of the students in writing short stories. It applied a qualitative and quantitative approach with tests and interviews as the instrument. The results showed that students had a